PENERAPAN METODE SMART READING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DI KELAS II SD NEGERI 13 SUNGAI KAWAT TAHUN PELAJARAN 2021/2022 - Dwi Cahyadi Wibowo; Putri Anggraini; Tedi Suryadi; Imanuel Sairo Awang (STKIP Persada Khatulistiwa Sintang, 2022)
This research was motivated by the researcher at SD Negeri 13 Sungai Kawat regarding students in grade II who were identified as having a deficiency in reading ability. Students in class II find it difficult to recognize letters and have difficulty arranging words in reading. So far, in learning to read at SD Negeri 13 Sungai Kawat, they still use an ineffective method, namely the common (ordinary) reading method. It makes students' reading ability low. The purpose of the study was to describe the improvement of students' reading ability using the smart reading method for class II SD Negeri 13 Sungai Kawat. This study used a qualitative descriptive approach and a form of classroom action research. The implementation process consists of 4 stages: planning, implementing actions, observing, and reflecting. The subjects in this study were second-grade students of SD Negeri 13 Sungai Kawat with six students, consisting of 2 male students and four female students. Data collection techniques used direct observation techniques, performance test techniques, and documentation techniques. The observations in cycle I students obtained an average score of 68.33% with sufficient criteria. Cycle II obtained an average score of 90% with very good criteria. The observations of teacher activities obtained an average score of 88.33 with good criteria, and cycle II obtained an average score of 98.33 with very good criteria. It shows that the application of the smart reading method is going very well. The pre-cycle reading ability test showed students obtained a class average of 52.66 with fewer criteria, the first cycle obtained a grade average of 76.5 with good criteria, then continued in the second cycle obtained a class average of 90.33 with very good criteria. The increase in reading ability increased by 13.83. It shows that the ability to read using the smart reading method is successful and increasing. It can be concluded that the application of the smart reading method can improve reading skills in grade II SD Negeri 13 Sungai Kawat for the 2021/2022 academic year.